Student Perceptions towards Supporting Learning Factors in Skills Lab - Fawzia, Farha Naily; Probandari, Ari Natalia; Suyatmi, . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Introduction: Clinical skills competence is one of areas of competence to be achieved by graduate of medical education institutions. As an effort to achieve clinical skills competency for the students, Medical Faculty of Universitas Sebelas Maret (UNS) establishs Skills Lab. In learning clinical skills, there are various components that can support learning. Therefore this study aimed to explore studentsâ perceptions of the supporting learning factors in the Skills Lab. Methods: This study was a qualitative research which conducted in Medical Faculty of Universitas Sebelas Maret on October-November 2016. The study participants were the second year, third year, and fourth year students of Medical Faculty of Sebelas Maret University. The method of collecting data was by focus group discussion (FGD) and in-depth interview. The data was analyzed by content anaylis. Data validation using triangulation method, peer debriefing, and member checking. Result: There are various factors influencing on learning in Skills Lab. Several factors were found in this study was instructor, curriculum, students, modules, infrastructure, and system in Skills Lab. According to student, an instructor must have a good character, good communication and interpersonal skills, competence in science, and have the appropriate skills and methods in teaching. In supporting learning, Skills Lab and blocks curriculum should be integrated and aligned. In addition, curriculum also has to be up to date with the development of the medical world. Students themselves have an influence in creating an effective learning. Students ideally should have motivation, adequate prior knowledge, and the attitudes and behavior in both the teaching and learning activities. Modules as well as infrastructure in the Skills Lab also act as a support when such facilities are available and adequate. System in Skills Lab is equally important. Various supporting activities such as monitoring-evaluation activities, and training of instructors need to be improved. Conclusion: In the perspective of a student, there are various factors that influence learning, including the instructors, curriculum, students, modules, infrastructure, and system in the Skills Lab. Keywords: supporting learning factors, Skills Lab, skills learningÂ